Environmental drivers modelling the mangrove Kinorhyncha community along an urban-to-natural gradient in French Guiana (western Atlantic Ocean) - Cepeda, Diego; Sánchez, Nuria; Spedicato, Adriana; Michaud, Emma; Zeppilli, Daniela (Frontiers in Marine Science, 2024)
Meiofaunal communities are dominated by free-living nematodes and harpacticoid copepods. Most of the studies defining the environmental drivers that influence meiofauna focus on these profuse groups. The ‘rare’ meiofaunal organisms (densities <5%) are frequently overlooked, making it difficult to know which abiotic variables influence their populations, or their ecological role in the benthic ecosystems. In this study, we explore the ecological factors that characterize a low human-polluted mangrove in French Guiana (western Atlantic Ocean) along an urban-to-natural gradient, focusing on the ‘rare’ phylum Kinorhyncha. This taxon seems to be mainly influenced by sediment size, being more abundant in silty sediments. The presence of microorganisms also enhances the community, likely due to a higher food availability. Oppositely, some trace metals of both lithogenic and anthropogenic origin, as well as predominance of coarser sediment particles, seem to negatively affect their populations. The importance of including the lesser abundant groups of meiofauna in ecological studies is evident, since it allows to have a better idea of the ecological state of marine benthic environments.